Cases of acute coronary syndrome - analysis of interventions of Emergency Medical Services Teams - Patryk Rzońca; Maja Chrzanowska-Wąsik; Mariusz Goniewicz; Kamil Bednarz; Karol Góra (Kazimierz Wielki University, 2017)
Diseases of the circulatory system in adults has been the most common cause of death for a long time. Despite the fact that statistically the number of people affected by those diseases is decreasing over the years, the epidemic of obesity and diabetes has a great impact on accelerated developing of atherosclerotic cardiovascular disease and its complications, such as angina pectoris and heart attack. The aim of this paper is to analyse the cases of acute coronary syndrome, which Emergency Medical Services Teams were dispatched to. The study was conducted using medical records collected within the period of one year (01.01.2014 - 31.12.2014) by the Regional Ambulance Service in Lublin. The study confirmed that men living in cites are at the highest risk of developing acute coronary syndrome. Among women the symptoms occur at an older age.